Centrifuge modelling of caisson breakwater subject to wave-breaking impacts - Zhang, X.Y.; Leung, C.F.; Lee, F.H. (Ocean engineering, 2009)
Model tests were conducted to investigate the behaviour of caisson breakwater resting on sand beds subject to impacts due to wave breaking. The centrifuge modelling technique was employed to simulate the prototype stress levels in the foundation soil as the behaviour of sand is highly stress dependent. A wave actuator was developed to simulate the wave-breaking impact loads on the caisson during centrifuge flight. The test results reveal that the vertical and horizontal movements and tilt of the caisson breakwater increase progressively with the number of breaking-wave impacts. The excess pore pressures developed in the foundation sand under non-reversal loading are generally small and appear insignificant. The results of the parametric studies conducted to examine the effects of impact-load pattern, caisson width, rock berm beneath caisson, wave slamming on top slab of caisson and cyclic preloading on the performance of caisson breakwater are also presented. The practical implications of the experimental findings in the present study are also highlighted in this paper.